Check Marks for the Knowledge of Ageing : Working for a Change in North Karelia! - Nuutinen, Teija; Jämsén, Arja (North Karelia University of Applied Sciences, 2012)
This publication analyses the topical concept of knowledge of ageing and invests the phenomenon with concrete content. The knowledge of ageing is a strong term that communicates positive opportunities. In North Karelia, the knowledge of ageing is highlighted in development targets for work with the elderly, curricula and strategies. The Centre for Social Services and Health Care in North Karelia University of Applied Sciences and the Eastern Finland Centre of Excellence on Social Welfare together with their partners have focused on building up the knowledge of ageing. The knowledge of ageing is understood as knowhow of social and health care field professionals concerning phenomena associated with age and ageing. However, the need for knowledge of ageing extends to all areas in society. This publication collects and analyses the knowledge of ageing in the ”merrily ageing” North Karelia. Dozens of workshop participants have been involved in shaping the concept and content of knowledge of ageing for several years. In this, the new roles and competences of professionals, senior citizens who are themselves active and participants in various communities, and a meaningful everyday life that is worth living are particularly prominent. The publication wishes to raise debate on the kind of ageing society we wish to build. The reader is also offered an opportunity to consider how and in what type of an environment he or she would personally like to grow old. The publication is suitable for professionals and students of various fields and all those interested in an ageing society and the knowledge of ageing.